Prevalence of polyoma BK virus infection among living‐donor renal transplant recipients. Issue 4 (29th July 2016) - El Ansary, M.; Abd Elhamid, S.; Saadi, G.; Ismail, W.; Ibrahim, N.; Bahaa El‐Din, N.; Alhsyek, S.
Abstract: Background: Polyomavirus nephropathy (PVN) mainly caused by BK polyomavirus (BKPyV) remains the most common productive viral infection of the kidney in immunosuppressed patients. The diagnosis of PVN is based on the detection of BK viruria and BK viremia in conjunction with histological findings in the graft biopsy. Methods: Our study was aimed to estimate the prevalence of productive BKPyV infection among renal transplant patients within the first year post‐transplant and identify those at risk of developing PVN. Our cross‐sectional study was conducted on 134 kidney transplant patients. Evidence of BKPyV replication was assessed by viral quantification of blood and urine samples of studied patients using a quantitative real‐time polymerase chain reaction (Q‐PCR)PCR), detection of decoy cells in urine cytology smears, histological examination of graft biopsies from Q‐PCR BKPyV‐positive patients, and immunohistochemical staining by simian virus 40 (SV40) antibody. Results: Significant BKPyV infection was prevalent in 8% ( n = 11) of our patients, with a peak of BKPyV infection about 8 months post transplant. BKPyV viral load by Q‐PCR assay in these patients varied from 1350 to 20, 000, 000 (1.35 × 10 3 to 2 × 10 7 ) copies/mL for urine samples and 935 to 18, 920 (9.35 × 10 2 to 1.89 × 10 4 ) copies/mL for blood samples. All the 11 patients were positive for decoy cells but only 3 developed PVN based on histology and positive SV40 staining. BKPyV infection was more prevalent in older patients. All patients responded to reduction in their immunosuppressive regimens, apart from 2 patients who required replacement of calcineurin inhibitors‐based regimen with mammalian target of ramapycin inhibitors with an overall good response. Conclusion: Protocol screening programs based on detection of viral replication by viruria, viremia, and decoy cells in urine are necessary to shed light on patients with high virus replication and hence increased risk of developing PVN, and to allow early diagnosis and intervention.